Effect of short courses on perception to use of ultrasound in trauma and ICU settings - Thapa, Amit; KC, Bidur; Shakya, Bikram (Journal of Kathmandu Medical College, 2018)
Background: Since 2012 we have been routinely conducting Kathmandu Medical College Teaching Hospital Ultrasound Trauma Life Support (KUTLS) courses. Unlike detailed examination of an organ with an ultrasound as performed by radiologist, we profess sonoscopic based problem solving approach for the clinician as he uses his stethoscope. The initial skepticism to use of sonoscope in a systematic methodical way has been seen to be fading. Objectives: We conducted a survey to see the change in knowledge and attitude of the clinicians to use of sonoscopy after a short focused but systematic training program. Methodology: We studied the questionnaire based feedback forms of the participants in the last 5 course of Kathmandu Medical College Teaching Hospital Ultrasound Trauma Life Support (KUTLS) workshop and analyzed the change in perception and understanding as well as improvement in scores of the post test. Results: A total of 152 delegates actively participated in five sessions workshops since 2012. The most common reasons to attend the workshop was to develop the skill with sonoscope, 95% participant did not have any past experience of sonoscopy. Almost 98% scored more than 75% in the post-workshop test compared to only 33% in the pre-workshop test suggesting fast learning curve among the learners. Almost 100% were convinced with the applicability of the USG and had wished to change their practice. Conclusion: A structured use of sonoscope would be helpful in clinical practice particularly in solving difficult questions urgently in trauma and Intensive Care Unit. Workshops and seminars help change attitude and practice of the participants even with no prior formal training in ultrasound.